BARRIERS AND FACILITATORS TO WRITE GOOD QUALITY MCQS FOR DENTAL ASSESSMENTS: A QUALITATIVE CASE STUDY - Aziz, Anbreen; Jaffer, Moneezhay; Qaiser, Aasma; Siddique, Lubna; Ali, Sarah (Journal of Ayub Medical College Abbottabad, 2022)
Background: To explore barriers and facilitators to write good quality items for undergraduate dental assessments. Methods: A qualitative case study was conducted from Feb-April 2021. Semi-structured interviews were conducted with a purposive sample of eighteen item writers from a public-sector dental institute of Rawalpindi, Pakistan. The data were transcribed verbatim and thematically analyzed to extract themes regarding barriers and facilitators to write good quality items. All quality assurance procedures of qualitative research were ensured during the research process. Results: Five themes related to barriers and three themes related to facilitators to write good quality items emerged from the data. The participants reported more barriers such as lack of frequent training and lack of peer review and feedback. Other barriers were demotivation due to lack of acknowledgement or monetary incentives, lack of content and construct expertise, clinical workload, and contextual barriers such as lack of internet facility, outdated library, and lack of place and time allocation for item construction. Facilitators were availability of peer review, feedback from post-hoc analysis, motivation due to the senior designation, clinical experience, and ample time for basic sciences faculty. Conclusion: Frequent item writing training, strong peer review process, pre-exam item vetting by the dental education department, and institutional improvements such as striving for content experts, time and place allocation for item construction, internet facility, updated library, and equal distribution of workload among faculty could enhance the quality of items. Moreover, ways to inculcate motivation among item writers such as appreciation or monetary incentives could be used to improve the quality of undergraduate assessments.